Morphology-controlled Au nanostructures for efficient and selective electrochemical CO2 reduction. Issue 12 (7th March 2018) - Kim, Jaehoon; Song, Jun Tae; Ryoo, Hyewon; Kim, Jin-Gyu; Chung, Sung-Yoon; Oh, Jihun
Abstract : Morphology-controlled Au nanostructures are fabricated via electroreduction of anodized Au thin films, exhibiting efficient catalytic activity for electrochemical CO2 reduction. Abstract : Electrochemical conversion of CO2 has been considered as a promising method for producing value-added chemicals. Here, we report a systematic study on the formation of Au nanostructures via electroreduction of anodic Au(OH)3 for selective CO production by an electrochemical CO2 reduction reaction (CO2 RR). First, we demonstrate the influence of electrochemical process parameters on the formation of Au nanostructures and Au(OH)3 . The Au nanostructure morphologies can be tuned into either pore-like or pillar-like structures by controlling the anodic potential and/or reduction current density. This distinctive morphology is associated with the electric-field-assisted transport of Au 3+ at/near the Au(OH)3 /Au interface. Additionally, we report the catalytic activity of the morphology-controlled Au nanostructures in the CO2 RR. Both Au nanostructures exhibit significantly higher CO selectivity at a low overpotential than the untreated Au film due to the high density of grain boundaries which can assist with faster stabilization of the CO2 ˙ − intermediate. In particular, the pore-like structures have a higher CO selectivity than the pillar-like ones at 280 mV overpotential although the pillar-like Au nanostructures have a higher CO selectivity and CO producing current density at high overpotentials. This potential-dependent CO2 RR performance of the two different Au nanostructures is discussed.